2009
DOI: 10.18553/jmcp.2009.15.8.648
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prescription Abandonment with Cost Share for High-Cost Specialty Pharmacy Medications

Abstract: BACKGROUND: In 2008, specialty medications accounted for 15.1% of total pharmacy benefit medication spending, and per member expenditures have increased by 11.1% annually from 2004 to 2008 within a commercially insured population of 8 million members. Insurers face increasing pressure to control specialty medication expenditures and to rely on increasing member cost share through creation of a fourth copayment tier within the incentive-based formulary pharmacy benefit system. Data are needed on the influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 5 publications
2
63
1
Order By: Relevance
“…A few PBMs have reported observational investigations of the association between out-of-pocket cost and medication use 27,29,30 or between medication adherence and all-cause health care costs. 31 In a balanced approach to VBID, a health plan-owned PBM advises against zero-dollar copayments because "even as little as $5 per prescription gives the benefit more perceived value to members;" suggests that plan sponsors "carefully consider whether value-based pharmacy benefits are a good fit" for members with adherence of less than 80% for medications to treat diabetes, high blood pressure, or dyslipidemia; and recommends that to improve cost-effectiveness, sponsors consider copayment reductions for generic drugs only.…”
mentioning
confidence: 99%
“…A few PBMs have reported observational investigations of the association between out-of-pocket cost and medication use 27,29,30 or between medication adherence and all-cause health care costs. 31 In a balanced approach to VBID, a health plan-owned PBM advises against zero-dollar copayments because "even as little as $5 per prescription gives the benefit more perceived value to members;" suggests that plan sponsors "carefully consider whether value-based pharmacy benefits are a good fit" for members with adherence of less than 80% for medications to treat diabetes, high blood pressure, or dyslipidemia; and recommends that to improve cost-effectiveness, sponsors consider copayment reductions for generic drugs only.…”
mentioning
confidence: 99%
“…The analysis found a significantly higher associated rate of prescription abandonment for MS patients paying more than $200 per prescription compared with patients paying $100 or less. 18 Our benchmark analysis of pharmacy and medical claims data showed that the mean out-of-pocket patient expenditure per prescription claim for MS agents increased from $48 per claim in 2006 to $82 in 2009 (Table 2). 7 Although the mean patient expenditure per prescription appears higher in 2010 than in 2009, the data are through 3 quarters and therefore are not representative of an entire year.…”
Section: Benefit Design Considerations and Member Cost Sharementioning
confidence: 97%
“…However, payers should exercise caution when utilizing a specialty tier and associated increased cost share. Gleason et al (2009) examined the rate of prescription abandonment in association with member cost share. 18 Members paying $100 or less per prescription for MS medications were compared with patients paying more than $100.…”
Section: Benefit Design Considerations and Member Cost Sharementioning
confidence: 99%
See 1 more Smart Citation
“…However, our research reported previously suggests that patient copayments greater than $100 per month for TNF blockers were associated with prescription abandonment. 45 …”
Section: ■■ Managed Care Considerationsmentioning
confidence: 99%